Implementation Of Central And Regional Financial Relations Policy On Regional Expenditure Management - Steven Howard Watumlawar; Julista Mustamu; Erick Stenly Holle (International Journal Of Economics Social And Technology, 2026)
The implementation of Law Number 1 of 2022 on Financial Relations between the Central Government and Regional Governments (HKPD Law) is expected to improve the quality of regional expenditure through stronger fiscal discipline and more efficient budget allocation. However, many local governments continue to face challenges in complying with the expenditure composition mandated by the law. This study examines the implementation of the HKPD Law in regional expenditure management in Tanimbar Islands Regency and identifies the factors influencing its implementation. An empirical legal approach was employed using interviews, questionnaires, and document analysis involving 33 respondents from the regional government, DPRD Budget Committee, BPKAD, and BAPPEDA. The findings reveal that the implementation of the HKPD Law has not been fully effective, as personnel expenditure continues to exceed the statutory threshold, thereby limiting infrastructure expenditure despite administrative compliance with mandatory spending in the education and health sectors. The study further identifies fiscal dependency on central transfers, limited technical capacity of financial management personnel, and the geographical characteristics of an archipelagic region as the principal barriers, while regulatory clarity and the utilization of the Regional Government Information System (SIPD) serve as important enabling factors. The novelty of this study lies in integrating juridical compliance analysis with empirical evaluation of regional expenditure management under the HKPD framework in a fiscally dependent archipelagic region. The findings contribute to the literature on fiscal decentralization and provide practical insights for strengthening regional fiscal governance through expenditure restructuring, institutional capacity enhancement, and improved implementation of the HKPD policy.